Cristalização, estrutura e atividade de duas proteínas com apelo biotecnológico: Pb27 de Paracoccidioides brasiliensis e salicilaldeído desidrogenase (NahF) de Pseudomonas putida - Juliana Barbosa Coitinho (2013)
According to the number of structures deposited on Protein Data Bank (PDB), the X-ray crystallography is the main method used to obtain structural information of biological macromolecules. Such information is useful for understanding the biological systems of which these macromolecules participate. In this study, two proteins with biotechnological interest were studied from the structural and biochemical view: the antigenic protein Pb27 from Paracoccidioides brasiliensis and the enzyme NahF from Pseudomonas putida. The fungus P. brasiliensis is the agent of one of the most important systemic mycoses in Brazil, paracoccidioidomycosis (PCM) and the protein Pb27, despite having been used with high sensitivity and specificity in the diagnosis and as an adjuvant in the treatment of PCM, Pb27s function is still unknown and this protein has no similar proteins with tertiary structure solved. Aiming to solve its structure by X-ray crystallography, recombinant Pb27 protein (Pb27r) was expressed in bacteria E. coli BL21(DE3) and purified by affinity chromatography and gel filtration, which was eluted with a volume equivalent to a monomer (24 kDa after removing the N-terminal Histag). Studies of dynamic light scattering (DLS) and circular dichroism (CD) revealed that protein is monodisperse and folded. Pb27 crystals were obtained in 0.25 M MgCl2, 25% PEG 4000, 100 mM Tris-Cl pH 7.0, with space group P212121 and diffracted up to 1.9 Å of resolution. In order to obtain crystals derivatives for solving the structure of Pb27r by anomalous scattering or isomorphous substitution it was performed soaking and co-crystallization with heavy atom salts (NaI, CsCl, GdCl3, Hg and Pt salts) were performed in addition to Se-Met labeling. However, derivative crystals with isomorphic/anomalous difference enough to determine Pb27 structure were not obtained yet.The NahF enzyme catalyzes the oxidation of salicylaldehyde to salicylate using NAD+ as a cofactor, the last reaction of the degradation upper pathway of naphthalene in P. putida. The naphthalene is the most abundant and toxic compound in oil and has been used as a model for bioremediation studies. To understand the structural determinants of activity of this enzyme, the recombinant protein NahF (NahFr) was expressed in E. coli Arctic Express at 12 oC and purified by affinity chromatography and gel filtration in which it eluted in three fractions. The main fraction contained the protein in its dimeric form and monodisperse (data obtained by DLS) and was used for kinetic and structural studies. NahFr was most active at pH 8.5 and 60 oC. EDTA, DTT and SDS inhibited the enzymatic activity while the Ni2+ increased by almost 20%. The enzyme showed high values of kcat/KM and preference for aromatic and long chain aliphatic aldehydes. The structure showed an / folding with the oligomerization, cofactor binding and catalytic domains well defined. The salicylaldehyde was present in a deep pocket in the structure where the catalytic Cys284 and Glu250 were seen. Moreover, the residues Arg157, Gly150 and Trp96 were important to specificity for aromatic aldehydes. The understanding of the characteristics of the enzyme NahF that are responsible for its activity and specificity and also its differences for other ALDHs from other organisms may open up possibilities for, for example, increased stability and other characteristics by systematic mutations, making it possible its use and other related enzymes in biotechnological processes